Command and Prohibition Utterances in Human Relationship being in Serat Wulang Reh as Javanese Local Wisdom Exploration Efforts - Siti Mulyani (Jurnal Penelitian Humaniora, 2015)
This study was aimed at expressing commands and prohibitions contained in Serat Wulang Reh. The object of this study was Serat Wulang Reh manuscript. The data of this study were lingual units that can be gatra (arranged) or the combination of gatra containing marker (symbol). The markers were analyzed based on the form of the basis word or derivatives of the basic words that contain af ixes and can be interpreted as a command or prohibition. The result shows that the use of markers to express commands from human to another human in Serat Wulang Reh are more varied than that are used to express prohibitions. The marker that is used to express a command has a different intensity; that are irm until fewer irms. The marker that is used to express prohibition must be avoided regarding the relationship between human with God and human’s relationship with each other has the same meaning. This is apparent on the lingual unit used by the following: aja jangan’, aywa ‘jangan’, dan nora kena ‘tidak boleh'